SWOT Analysis of Business Strategies in Indonesian Telecommunications Companies: A Case Study of PT Telkom Indonesia and PT Indosat Ooredoo Hutchison - Shifa, Mutiara; Ardiansyah, Ardiansyah; Mustaqim, Al; Muliana, Muliana; Sari, Cindi Permata (Riwayat: Educational Journal of History and Humanities, 2024)
Digital transformation has fundamentally reshaped the telecommunications industry, compelling companies to adapt through innovative and flexible strategies. This study compares the business strategies of PT Telkom Indonesia and PT Indosat Ooredoo Hutchison using a SWOT analysis integrated with the theories of dynamic capabilities and organizational ambidexterity. A qualitative and descriptive approach is employed to evaluate the strengths, weaknesses, opportunities, and threats of each company based on corporate documents, academic literature, and industry reports. The findings reveal that Telkom excels in infrastructure and Fixed Mobile Convergence (FMC) integration strategy, while Indosat demonstrates strengths in strategic partnerships and post-merger digital innovation. Both companies exhibit dynamic capabilities in the sensing and seizing phases but face challenges in the transforming phase when managing ambidexterity effectively. The study proposes SWOT-based strategies that support operational efficiency, digital ecosystem enhancement, and the development of an innovative and agile organizational culture. These findings are expected to contribute theoretically to strategic management literature and offer practical implications for Indonesias telecommunications sector in navigating digital disruption.